COLONIALISM AND PEASANT RESISTANCE IN SOUTHEAST ASIA - Putra Hidayatullah (Indonesian Journal of Islamic History and Culture, 2022)
Colonialism in Southeast Asia was marked by the response of local communities, especially farmers, in various forms of protest. The protests were rooted in problems with the economic system. The colonial rulers brought a different economic logic with a new mode of production for traditional farmers. In response to these protests, the colonial government was assisted by the presence of local elites. This article will describe peasant resistance in Indonesia, Vietnam and the Philippines with the argument that although local elites were involved, they had different ways of dealing with resistance. In addition to the problems of the economic system, colonialism also brought modernity which had an impact on the disintegration of the social system.